Evaluasi Keterampilan Menulis (Maharah Kitabah) dalam Buku Bahasa Arab Marhalah Tiga Pusat Bahasa UIN Sultan Syarif Kasim Riau Tahun 2018 - Salman Paris Nasution; Hikmah Hikmah; Masrun Masrun (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
The evaluation of textbooks is a strategic step to ensure the alignment of instructional materials with curricular goals and the needs of learners. In the context of teaching Arabic at the university level, writing skills (mahārah kitābah) are an essential component in shaping productive and communicative language abilities. This study aims to evaluate the representation and development of writing skills in the Arabic Language Book Marhalah Three, published by the Language Center of UIN Sultan Syarif Kasim Riau in 2018. The study employs a descriptive qualitative approach using a document analysis method. Data were collected through content analysis of the textbook using a foreign language textbook evaluation rubric, which includes aspects such as content, instructional approach, and the suitability of the material to students' competencies. The findings indicate that although the book is organized with a systematic instructional structure and thematically relevant content, the development of writing skills is still primarily based on a structural approach and lacks diverse, communicative exercises. These findings suggest the need for improvement in the textbook by integrating communicative, integrative, and contextual approaches in order to enhance the effectiveness of mahārah kitābah instruction in higher education settings.